Getting beyond "Jesuit Thinking". The "désenclavement" of Jesuit Studies Twenty Years on. Where We Are Now? A Consideration of: The Oxford Handbook of the Jesuits, edited by Ines G. upanov - Ditchfield, Simon (Journal of Jesuit studies, 2020)
"Getting beyond "Jesuit Thinking". The "désenclavement" of Jesuit Studies Twenty Years on. Where We Are Now? A Consideration of" published on 29 Jan 2020 by Brill.